A systematic literature review on the policies and economic evaluation of organ transplantations in EU - Georgia Tritaki; Paolo Di Giannantonio; Stefania Boccia (Epidemiology, Biostatistics and Public Health)
Background: transplantation of human organs and tissues saves many lives and restores essential functions in combination of high measurable quality indicators. In spite of the fact that organ transplants have saved thousands of lives and greatly improved the quality of life of thousands more, regrettably many people will not benefit from this therapeutic procedure. Methods: this review is based on economic evaluation studies published since 2000 and reviews published since 1987 for kidney, liver, lung, heart, pancreas, and small bowel transplantations that were conducted in 2010. Results: empirical evidence showed that the costs of organ transplantations have generally decreased over time due to improvements in medicine, while survival and quality of life have improved. This indicates that the cost-effectiveness of transplantation has also improved over this period. Conclusions: cost effectiveness studies on organ transplantations could contribute to the efforts of policy makers in maximising societal health benefits by managing society’s scarce resources. The differences between EU country are not only associated with different legal procedures but are also associated with social, organizational and several other factors.